1959
DOI: 10.2136/sssaj1959.03615995002300040024x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cotton and Corn to Deep Placement of Fertilizer and Deep Tillage

Abstract: Deep placement of fertilizer and deep tillage were evaluated as to their effect on crop yields and root development. Experiments conducted for several years on four soil types showed that greater root development in the subsoil and increases in yield may be expected from deep fertilizer placement and deep tillage on soils that possess traffic pans. This was particularly evident in years of below average rainfall, when the increased root development in the subsoil caused by deep placement of fertilizer or deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…However, based on seed cotton yield and leaf K concentrations, deep placement of K fertilizer proved no better than surface application and, in the one year measured, leaf deficiency symptoms were more severe when K was deep placed rather than surface applied. These results agree with those of Patrick et al (1959), who found no advantage to deep placement vs. surface placement of N-P-K fertilizer to corn (Zea mays L.) and cotton grown on a Gallion silt loam soil (finesilty, mixed, thermic, aerie Typic Hapludalfs) with a plowpan, provided the crops were all deep tilled. Our conclusions are also supported by recent work that showed cotton roots located 30 to 60 em deep were less effective in P uptake than roots in the surface 30 em of soil (Nayakekorala and Taylor, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…However, based on seed cotton yield and leaf K concentrations, deep placement of K fertilizer proved no better than surface application and, in the one year measured, leaf deficiency symptoms were more severe when K was deep placed rather than surface applied. These results agree with those of Patrick et al (1959), who found no advantage to deep placement vs. surface placement of N-P-K fertilizer to corn (Zea mays L.) and cotton grown on a Gallion silt loam soil (finesilty, mixed, thermic, aerie Typic Hapludalfs) with a plowpan, provided the crops were all deep tilled. Our conclusions are also supported by recent work that showed cotton roots located 30 to 60 em deep were less effective in P uptake than roots in the surface 30 em of soil (Nayakekorala and Taylor, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…In Louisiana, Patrick et al (1959) found that 0.3-m deep moldboard plowing or 0.35-m deep chiseling increased yields on silt loam soils that had high bulk density layers just below plow depth. When soil horizons below compacted zones were infertile or acidic, deep application of fertilizer or lime was beneficial.…”
Section: Plowpan Soilsmentioning
confidence: 99%
“…None of the soil types involved (seven in Iowa, five in Illinois) had pronounced plowpan layers, although subsoiling was a common crop production practice on these soils. Like Patrick et al (1959), they stated that deep application offertilizer and lime was beneficial when those amendments were needed. Deep tillage increased crop yields most when artificially produced compact zones were immediately below the plow layer.…”
Section: Plowpan Soilsmentioning
confidence: 99%
“…It had less effect on naturally compact soils, possibly because compact zones were too thick for tillage tools to completely penetrate them. Like Patrick et al (1959), they stated that deep application offertilizer and lime was beneficial when those amendments were needed. In Connecticut, De Roo (1961) found that shattering the plowpan produced only small increases in tobacco (Nicotiana tobacum) yields even though the plowpan severely limited penetration of roots.…”
Section: Plowpan Soilsmentioning
confidence: 99%